Navigating trade restrictions - Vasily Astrov; Carsten Brockhaus; Julian Hinz; Levke Jessen-Thiesen; Hendrik Mahlkow; Patrik Svab (The Vienna Institute for International Economic Studies (wiiw), 2024)
This report focuses on Russia's adaptation in its commodity exports during 2023, amidst ongoing international sanctions. It examines the shifts in export and maritime shipping patterns, emphasizing coal, crude oil, and liquefied natural gas, and their redirection towards alternative, non-sanctioning markets. The analysis details Russia's efforts to maintain its commodity exports by leveraging new maritime routes and - possibly - spoofing Automatic Identification System (AIS) signals to avoid detection of ship-to-ship transfers of oil.
Keywords: F14; F51; Q4; 330; commodity exports; maritime shipping; ship-to-ship oil transfers